Metabolic Food Waste and Ecological Impact of Obesity in FAO World's Region - Toti, Elisabetta; Di Mattia, Carla; Serafini, Mauro (Frontiers in Nutrition, 2019)
Obesity represents a titanic cost for the world’s health systems but also a substantial ecological cost to the environment. High energy foods have been shown to be the major contributor to Greenhouse Gases (GHGs) emissions, challenging the diet-environment-health triangle. The waste of resources and the unnecessary ecological cost due to an excessive consumption of foods leading to obesity have been ignored so far. Metabolic Food Waste (MFW(kg of food)), corresponds to the amount of food leading to Excess Body Fat (EBF) and its impact on environment, expressed as carbon (MFW(kgCO2eq)), water (MFW(x 10 L)) and land footprint (MFW(x10 m2)). We aim to estimate the MFW(kg of food) in the seven FAO regions, Europe (EU), North America & Oceania (NAO), Latin America (LA), Sub Sahara Africa (SSA), Industrialized Asia (IA), North Africa, West & Central Asia (NAWCA) and South & Southeast Asia (SSEA), and evaluate its impact on ecological footprints. The overall impact of MFW(tons of food) in the world correspond to 140.7 Gigatons associated to overweight and obesity. Between the different regions, EU is responsible of the greatest amount of MFW(tons of food) volumes (39.2 Gigatons), followed by NAO (32.5 Gigatons). In term of ecological impact, EU and NAO displayed the highest values for all three MFW footprints, about 14 times more than SSA. We provide evidences of the enormous amount of food lost through obesity and its ecological impact. Reducing metabolic food waste associated to obesity will contribute in reducing ecological impact of unbalanced dietary pattern through an improvement of human health.